Position paper: Sports psychiatric care provision in competitive sports - Claussen, M. C.; Gonzales Hofmann, C.; Schneeberger, A. R.; Seifritz, E.; Schorb, A.; Allroggen, M.; Freyer, T.; Helmig, F.; Niebauer, J.; Hefert, J.; Klostermeier, E.; Fröhlich, S.; et al. (Deutsche Zeitschrift für Sportmedizin, 2021)
Mental stress and illness are common health problems in competitive sports that can reduce performance and have effects beyond the end of a career as sport-specific and unspecific disorders.